2014
DOI: 10.3390/nu6020530
|View full text |Cite
|
Sign up to set email alerts
|

Low Blood Zinc, Iron, and Other Sociodemographic Factors Associated with Behavior Problems in Preschoolers

Abstract: Previous research supports the link among malnutrition, cognitive dysfunction, and behavioral outcomes; however, less research has focused on micronutrient deficiencies. This study investigates whether micronutrient deficiencies, specifically blood zinc and iron levels, will be associated with increased behavior problem scores, including internalizing and externalizing behaviors. 1314 Children (55% boys and 45% girls) from the Jintan Preschool Cohort in China participated in this study. Venous blood samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 53 publications
0
22
0
2
Order By: Relevance
“…Using the clinical reference range of 75–175 μg/dl (Liu et al, 2014), we found that both iron deficiency and high iron levels existed in our sample. This finding is consistent with a recent study in which researchers reported a double burden of under- and overnutrition of iron among Chinese children aged 2–12 years (Piernas et al, 2015).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Using the clinical reference range of 75–175 μg/dl (Liu et al, 2014), we found that both iron deficiency and high iron levels existed in our sample. This finding is consistent with a recent study in which researchers reported a double burden of under- and overnutrition of iron among Chinese children aged 2–12 years (Piernas et al, 2015).…”
Section: Discussionmentioning
confidence: 77%
“…We used the reference range recommended in Chinese hospitals to define iron levels. Specifically, we classified concentrations lower than 75 μg/dl as low iron level (iron deficiency), 75–175 μg/dl as middle level (normal iron), and those greater than 175 μg/dl as high iron level (Liu et al, 2014). …”
Section: Methodsmentioning
confidence: 99%
“…The sample characteristic, sleep status and blood zinc profile at preschool were presented elsewhere by our research team [ 19 , 25 ]. Between 2011 and 2013, participants were in their early adolescence aged from 11 to 15 years old.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies (Gleason et al 2011;Velders et al 2011;Liu et al 2014a) examined the effect of parental education on child's IEP. In two studies (Velders et al 2011;Liu et al 2014a) low maternal education is related to increases in IEP, and one found no significant results on IEP (Gleason et al 2011). Only one study (Gleason et al 2011) assessed the effect of paternal low education, finding significant results indicating that when the fathers have a low education level, children tend to present more IEP.…”
Section: Parental Education and Agementioning
confidence: 99%